Analysis of Individual Factors on the Usefulness of Trusted Information Systems at X Primary Clinic - Sholihah, Firdha Amaliatus; Sugiyanta, Sugiyanta; Asmaningrum, Nurfika (GLOBAL HEALTH SCIENCE GROUP, 2024)
Implementing SIM in Clinics as one of the FKTPs is very useful in providing health services. This study aims to analyze individual factors regarding perceived benefits through the intervening variable perceived ease of use of information technology at private clinics in Jember district. This quantitative research is analytical research with an observational approach. The population of this study was 46 employees at two private clinics who had SIMRS usernames. The sampling technique uses the total sampling method. Research data was obtained from the results of filling out questionnaires by respondents. Data analysis using the SmartPLS application with the Partial Least Square technique. The results show that Individual factors have a strong contribution to perceived ease of use and perceived usefulness.Individual factors have a positive effect on perceived ease of use with a path coefficient value of 0.427, a T-statistic value of 3.498.Individual factors have a positive effect on perceived usefulness with a path coefficient value of 0.077. The path coefficient value of 0.844 shows that there is a strong and positive influence between perceived convenience on perceived usefulness with a high T-statistic value (11.177).Individual factors influence perceived usefulness through the intervening variable perceived ease of use.